Uneven distribution of prokaryote-derived horizontal gene transfer in fungi: a lifestyle-dependent phenomenon - Fei Liu; Shi-Hui Wang; Ratchadawan Cheewangkoon; Rui-Lin Zhao (mBio)
ABSTRACT Horizontal gene transfer (HGT) in fungi is less understood despite its significance in prokaryotes. In this study, we systematically searched for HGT events in 829 representative fungal genomes. Using a combination of sequence similarity and phylogeny-based approaches, we detected 20,093 prokaryotic-derived transferred genes across 750 fungal genomes, via 8,815 distinct HGT events. Notably, our analysis revealed that eight lifestyle-related traits significantly influence HGT diversity in fungi. For instance, parasites exhibited the highest estimated number of HGT-acquired genes, followed by saprotrophs, with symbionts showing the lowest. HGT-acquired genes were predominantly associated with metabolism and cellular functions and underwent purifying selection. Moreover, horizontally transferred genes with introns have significantly higher expression levels compared to intron-lacking genes, suggesting a probable role of intron gains in the adaptation of HGT-acquired genes. Overall, our findings highlight the influence of lifestyle on HGT diversity in fungi and underscore the substantial contribution of HGT to fungal adaptation.IMPORTANCEThis study sheds new light on the role of horizontal gene transfer (HGT) in fungi, an area that has remained relatively unexplored compared to its well-established prevalence in bacteria. By analyzing 829 fungal genomes, we identified over 20,000 genes that fungi acquired from prokaryotes, revealing the significant impact of HGT on fungal evolution. Our findings highlight that fungal lifestyle traits, such as being parasitic or saprotrophic, play a key role in determining the extent of HGT, with parasites showing the highest gene acquisition rates. We also uncovered unique patterns of HGT occurrence based on fungal morphology and reproduction. Importantly, genes with introns, which are more highly expressed, appear to play a crucial role in fungal adaptation. This research deepens our understanding of how HGT contributes to the metabolic diversity and ecological success of fungi, and it underscores the broader significance of gene transfer in shaping fungal evolution.